The utilization of backgrounds as radiating elements to construct multibeam radial line slot array (RLSA) antennas - Purnamirza, Teddy; Nawawi, Ahmad; Mohd Ibrahim, Imran; Rahmi, Depriwana (Praise Worthy Prize, 2021)
RLSA antennas normally have a single beam produced by slots installed on their radiating element. A technique was, therefore, introduced in this study to optimally design multibeam RLSA antennas. This involved the utilization of the antennas’ background to radiate signals by installing slots on it just like the radiating element to ensure the creation of multibeam after which the effects of this method such as signal flow disturbances and gain reduction were discussed. Moreover, 105 multibeam RLSA models were designed and simulated to verify the technique developed after which a prototype of the best model was fabricated and measured to verify the simulation. The result showed it is possible to obtain multibeam antennas with similar symmetry in terms of beamwidth and directions. Furthermore, the gain recorded for beams 1, 2, 3, and 4 was 8.28 dBi, 6.28 dBi, 6.38 dBi, and 8.18 dBi respectively, and were averagely about 6 dB lower than the value for single beam RLSA antennas, therefore, they suit the theory of beam splitting. The antennas were also found to have more than enough bandwidth and good reflection coefficient and the technique’s validity was verified by a strong agreement between the simulation and measurement results.